2018
DOI: 10.1016/j.humpath.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Benign vascular tumors, cysts, and pseudocysts of the adrenal gland: a contemporary multi-institutional clinicopathological analysis of 55 cases

Abstract: Benign adrenal vascular tumors, cysts and pseudocysts are a heterogeneous group of relatively uncommon entities that may pose diagnostic challenges radiologically and pathologically. However, there are only a few small cases series, systematically characterizing the clinicopathologic features of these lesions. We identified 55 cases of benign adrenal vascular tumors, cysts and pseudocysts (23 pseudocysts, 17 hemangiomas, 8 lymphangiomas, 6 angiomatous endothelial cysts and 1 arteriovenous malformation) from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
1
17
1
Order By: Relevance
“…There are four classes of adrenal gland cysts: epithelial, endothelial, and parasitic and pseudocysts but they can also become haemorrhagic 2 . A review of 8 cases in a study in the United States revealed lesion sizes ranging from 1.8-10cm, though the size of the lesion does not correlate with symptoms, but in our case report the lesion was larger 3 . They are often seen in the 5th and the 6th decades of life, but can also be diagnosed during pregnancy 13,14,16 .…”
Section: Introductioncontrasting
confidence: 69%
See 2 more Smart Citations
“…There are four classes of adrenal gland cysts: epithelial, endothelial, and parasitic and pseudocysts but they can also become haemorrhagic 2 . A review of 8 cases in a study in the United States revealed lesion sizes ranging from 1.8-10cm, though the size of the lesion does not correlate with symptoms, but in our case report the lesion was larger 3 . They are often seen in the 5th and the 6th decades of life, but can also be diagnosed during pregnancy 13,14,16 .…”
Section: Introductioncontrasting
confidence: 69%
“…Haemorrhagic adrenal cysts are rarely symptomatic and often found incidentally during surgery for other conditions or at autopsy, except when they are large as in the case of a giant adrenal pseudocyst which was surgically removed 1,3 . The search on pseudocysts also revealed only a few cases documented over several years, often detected at pathological examinations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cysts are lined by a single layer of bland, flattened endothelial cells and are subcategorized into lymphangiomatous and angiomatous types. Immunohistochemically, all endothelial cysts are positive for CD31, CD34, and ERG, while lymphangiomatous cysts selectively stain for D2-40 (Zheng et al 2018) (Fig. 1).…”
Section: Microscopymentioning
confidence: 98%
“…Benign adrenal vascular pathologies, including tumors, cysts, and pseudocysts, are relatively rare entities that are mostly right-sided and predominantly observed in females [1]. These lesions may occur concomitantly with other adrenal tumors associated with hormone secretion.…”
Section: Introductionmentioning
confidence: 99%